2019
DOI: 10.1055/s-0039-1693119
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Review of Contemporary Evidence for the Management of T1 Renal Cell Carcinoma: What IRs Need to Know for Kidney Cancer Tumor Boards

Abstract: Renal cell carcinoma is a relatively common malignancy, with 60 to 70 thousand cases a year in the United States alone. Increased utilization of cross-sectional imaging has led to an increase in the number of early renal cell cancers seen by the medical establishment. In addition, certain patient populations have an increased risk of developing kidney cancers which may mandate aggressive screening protocols. This article discusses the epidemiology of renal cell cancers; discusses the current management guideli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 94 publications
1
7
0
Order By: Relevance
“…A technical success, referred to as the complete covering of the lesion by the ice ball on the first post-procedural scan, was achieved in 171 of 174 lesions (98.3%). These results compare favorably with the 94% reported in the study by Cronan et al [ 8 ] and is in line with the rate of 98.9% reported in a recent series by Lim et al [ 39 ]. In general, this outcome depends on technique-related factors like probe positioning, correct completion of the cycles, and visual control of the ice ball [ 10 ].…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…A technical success, referred to as the complete covering of the lesion by the ice ball on the first post-procedural scan, was achieved in 171 of 174 lesions (98.3%). These results compare favorably with the 94% reported in the study by Cronan et al [ 8 ] and is in line with the rate of 98.9% reported in a recent series by Lim et al [ 39 ]. In general, this outcome depends on technique-related factors like probe positioning, correct completion of the cycles, and visual control of the ice ball [ 10 ].…”
Section: Discussionsupporting
confidence: 93%
“…This study showed a local recurrence rate of 2.9% at one year, of 2.9% at three years, and of 1.8% at five years, appearing consistent with some studies establishing a local recurrence rate between 0% and 5% in the first three years of follow-up [7,10,12,17,29] and significantly lower compared to others that report recurrence rates ranging from 7% to 16% [6,9,16,42,44,45] at three years. Similarly, long-term results are strongly encouraging, showing a local recurrence at five years of 1.8% against the 3% evident in some studies [8,46] and even 13% in other series [16,42,43].…”
Section: Discussionmentioning
confidence: 73%
See 3 more Smart Citations